STRATEGI DINAS PEMBERDAYAAN MASYARAKAT DESA DALAM PENGARSIPAN DOKUMEN LAPORAN DESA DI KABUPATEN SIMEULUE - Tetty Kisniati Br Ujung; Fadhil Ilhamsyah (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2023)
This study discusses the design of a manual archive system in the Simeulue Regency Village Community Empowerment Service in the field of Mukim and Village Community Empowerment where the design of an archive system is made to store documents and management is done manually. The aim of the research is to make the filing system more structured, maintained, organized and documents easy to find when needed so that it makes it easier for services in the filing field as well as makes it easier for employees to find documents that will be used or needed again and documents can be managed better by supervising and checking documents for this research method using qualitative research methods with a descriptive approach, this approach was chosen because the research was carried out directly to see the topics to be examined, conducted question and answer observations regarding the document administration process then, carried out a report document archiving strategy by making archival designs . Data collection techniques by means of observation, interviews, document data related to DPMD. The design of the archive system is the creation or drawing of a form that has the aim of meeting the needs of the archives in the Office. Archives are a proof or as a reminder that a report or document has arrived to an agency or service where one day the documents will be needed again. Archives are a requirement that has a function as storage, management, and retrieval of needed archives.